Extrakorporale Nierenersatztherapie bei akuter Nierenschädigung: Empfehlungen der Sektionen „Niere“ der DGIIN, ÖGIAIN und DIVI = Extracorporeal renal replacement therapy in acute kidney injury - Schwenger, Vedat; Kindgen-Milles, D.; Willam, C.; Jörres, A.; Druml, W.; Czock, David; Klein, S. J.; Oppert, M.; Schmitz, M.; Kielstein, J. T.; Zarbock, A.; Joannidis, M.; et al. (Medizinische Klinik, Intensivmedizin und Notfallmedizin, 2018)
BackgroundAcute kidney injury (AKI) is a common complication in intensive care unit (ICU) patients. The incidence of AKI in ICU patients exceeds 50% and the associated morbidity and mortality rates increase with severity of AKI. In addition, long-term consequences of AKI are underestimated and several studies show impaired long-term outcome after AKI. In about 5-25% of ICU patients with AKI renal replacement therapy (RRT) is required.ObjectivesTo assist in indication, timing, modality and application of renal replacement therapy of adult patients, current recommendations from the renal sections of the DGIIN (Deutschen Gesellschaft für Internistische Intensivmedizin und Notfallmedizin), ÖGIAIN (Österreichischen Gesellschaft für Internistische und Allgemeine Intensivmedizin und Notfallmedizin) and DIVI (Deutschen Interdisziplinären Vereinigung für Intensiv- und Notfallmedizin) are stated.Materials and methodsThe recommendations stated in this paper are based on the current KDIGO (Kidney Disease: Improving Global Outcomes) guidelines, recommendations from the 17th Acute Disease Quality Initiative (ADQI) Consensus Group, the French Intensive Care Society (SRLF) with the French Society of Anesthesia Intensive Care (SFAR) and the expert knowledge and clinical experience of the authors.ResultsToday, different treatment modalities for RRT are available. Although continuous RRT and intermittent dialysis therapy as well as continuous dialysis therapy have comparable outcomes, differences exist with respect to practical application as well as health-economic aspects. Individualized risk stratification might be helpful to choose the right time to start and the right treatment modality for patients.